Security, Investment and Economic Growth in Sub-Saharan Africa - Tapsoba, Habibou; Zahonogo, Pam; Aïhounhin, Sègbédji Parfait (Journal of Applied Business and Economics, 2020)
This paper analyses the relationship between security and economic growth through investment, in 28 countries in Sub-Saharan Africa (SSA). The analysis of this relationship is done using the model of Borensztein et al. (1998) and uses data for the period 1996-2015. Estimation is done by the system generalized method of moments (GMM). The results show that security positively influences the level of economic growth in SSA countries both through domestic investment and Foreign Direct Investment (FDI). The study therefore recommends that policies to support economic growth should incorporate security provisions such as guaranteeing property rights, strengthening the quality of institutions and reducing armed conflict in the area.